Non-Invasive Probing of Nanoparticle Electrostatics - Tschulik, K; Cheng, W; Batchelor-McAuley, C; Murphy, S; Omanovic, D; Compton, R (2015)
© 2015 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim. Electrostatic interactions between surface-charged nanoparticles (NPs) and electrodes studied using existing techniques unavoidably and significantly alter the system being analyzed. Here we present a methodology that allows the probing of unperturbed electrostatic interactions between individual NPs and charged surfaces. The uniqueness of this approach is that stochastic NP impact events are used as the probe. During a single impact, only an attomole of the redox species reacts and is released at the interface during each sensing event. As an example, the effect of electrostatic screening on the reduction of negatively charged indigo NPs at a mercury microelectrode is explored at potentials positive and negative of the potential of zero charge. At suitable overpotentials fully driven electron transfer is seen for all but very low (<0.005M) ionic strengths. The loss of charge transfer in such dilute electrolytes is unambiguously shown to arise from a reduced driving force for the reaction rather than a reduced population of NPs near the electrode, contradicting popular perceptions. Electrostatics were found not to significantly affect the reactivity of the studied NPs. Importantly, the presented technique is general and can be applied to a wide variety of NPs, including metals, metal oxides and organic compounds. Not what you might think: A new and non-invasive technique to probe the electrostatic interaction between surface-charged nanoparticles and a charged metal/solution interface shows that electrostatic effects are insignificant in all but very dilute electrolytes.